World Allergy Organization Study on Aerobiology for Creating First Pollen and Mold Calendar With Clinical Significance in Islamabad, Pakistan; A Project of World Allergy Organization and Pakistan Allergy, Asthma & Clinical Immunology Centre of Islamabad - Shahid Abbas, MBBS, MSc, DCP (World Allergy Organization Journal, 2012)
Pollen and mold allergies are highly problematic in Islamabad. This study was conducted to investigate the type and concentration of airborne pollens/molds causing allergic diseases in susceptible individuals. A volumetric spore trap (Burkard) was placed at the height of 11 m and ran continuously for 3 years. Once a week, the collecting drum was prepared by affixing Melinex tape with a double sided adhesive that was coated with a thin layer of silicone grease. Every Sunday at 9:00 AM the drum was replaced by another drum and the pollen/mold spores were removed and permanently mounted on slides. Using a microscope, the trapped particles were identified and recorded as counts per cubic meter of air per hour. From these data, the pollen and mold calendars were constructed and expressed as counts per cubic meter of air per day. Skin prick tests were performed on more than 1000 patients attending the Pakistan Allergy, Asthma & Clinical Immunology Centre of Islamabad. The results indicated that there were 2 main pollen plants that contributed to seasonal allergies. These were Broussonetia papyrifera and Cannabis sativa during the March/April season and the July/September season, respectively. Although mold spores were continuously detected throughout the year, the most prominent mold was undetected mold and unconfirmed mold species similar to Stachybotrys species, which was high from July to September/October. Two additional molds contributing to allergic reactions were Pithomyces species and Cladosporium species, which were active during January and April, with the latter also being detected between October and November. These results may prove beneficial to both patients and physicians in planning a therapeutic protocol for avoidance and amelioration. Keywords: pollen and mold calendar, aerobiology, Islamabad, Burkard spore trap, Broussonetia papyrifera, Cannabis sativa, skin prick test, SPT, asthma, allergic rhinitis